2021
DOI: 10.1007/s11357-021-00474-3
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte-derived ratios are associated with late-life any type dementia: a cross-sectional analysis of the Mugello study

Abstract: Immunosenescence, vascular aging, and brain aging, all characterized by elevated levels of inflammatory markers, are thought to share a common pathogenetic pathway: inflamm-aging. Retrospective cross-sectional analysis was conducted using data from the Mugello study (Tuscany, Italy), a representative Italian cohort of free-living nonagenarians. to assess the association between specific peripheral inflammation markers derived from white blood cell counts, and the diagnosis of dementia. All the variables of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…However, the odds of cardiovascular events in patients with early coronary heart disease manifestations were the highest in patients with an elevated LMR [ 38 ]. Lombardi et al also found that a higher LMR is directly associated with any type of clinical diagnosis of dementia [ 39 ]. Additionally, our study confirmed that a higher LMR value was an independent risk factor for PI.…”
Section: Discussionmentioning
confidence: 99%
“…However, the odds of cardiovascular events in patients with early coronary heart disease manifestations were the highest in patients with an elevated LMR [ 38 ]. Lombardi et al also found that a higher LMR is directly associated with any type of clinical diagnosis of dementia [ 39 ]. Additionally, our study confirmed that a higher LMR value was an independent risk factor for PI.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Standard laboratory procedures for quality control were strictly followed. 9–11 , 13 Leukocyte-derived ratios were defined as follows: NLR= NE/LYM, dNLR= NE /[WBC-NE], MLR= MO/LYM, PLR= PLT/LYM, WMR= leukocyte/mean PLT volume, MNM= LYM × NE/10 4 , SIRI= NE × MO/LYM, and SII = PLT/NE/LYM.…”
Section: Methodsmentioning
confidence: 99%
“…19 Standard laboratory procedures for quality control were strictly followed. [9][10][11]13 Leukocyte-derived ratios were defined Hospital professionals also measured the color Doppler ultrasound of the carotid artery after the patient was rested in a supine position for approximately 15 min. Bilateral common carotid arteries, bifurcation, and the internal and external carotid arteries were scanned along the direction of the blood vessels to determine the intima-media thickness (IMT).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dementia patients were older, had suffered stroke more frequently, and had higher peripheral blood lymphocyte counts and a higher lymphocyte-to-monocyte ratio. These results suggest a possible influence of the immune system, but further phenotyping on immune cells was not available [ 56 ]. One of the first studies on immunosenescence compared immunological functions in AD with elderly and young controls.…”
Section: Methodsmentioning
confidence: 99%